PEMANFAATAN LAHAN PEKARANGAN DALAM MENINGKATKAN PENDAPATAN KELUARGA DI KECAMATAN ASERA KABUPATEN KONAWE UTARA - Rostin, Rostin; Putera, Asrip; Anto, Rola Pola; Yunila, Yunila; Dewi, Made Listia; Rahayu, Sara Evi (Yayasan Education and Social Center, 2024)
One of the strategies of the North Konawe Regency Regional Government in encouraging the use of existing resources in order to increase community income is to maximize the function of yard land which has been